2020
DOI: 10.1177/2325967120950306
|View full text |Cite
|
Sign up to set email alerts
|

An Up-to-Date Review of the Meniscus Literature: A Systematic Summary of Systematic Reviews and Meta-analyses

Abstract: Background: A large number of systematic reviews and meta-analyses regarding the meniscus have been published. Purpose: To provide a qualitative summary of the published systematic reviews and meta-analyses regarding the meniscus. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic search of all meta-analyses and systematic reviews regarding the meniscus and published between July 2009 and July 2019 was performed with PubMed, CINAHL, EMBASE, and the Cochrane database. Published abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 142 publications
1
33
0
Order By: Relevance
“…Evidence from randomized controlled trials (RCT) has suggested that partial meniscectomy may not be superior to non-surgical care alone or sham surgery, but some trials had important study design limitations and high cross-over rates [1,7,27,32,33,35,36]. Nonetheless, expert consensus statements and professional societies recommend partial meniscectomy for patients with irreparable meniscus tears and mechanical knee symptoms that are refractory to at least 3 months of non-surgical care [5,19].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from randomized controlled trials (RCT) has suggested that partial meniscectomy may not be superior to non-surgical care alone or sham surgery, but some trials had important study design limitations and high cross-over rates [1,7,27,32,33,35,36]. Nonetheless, expert consensus statements and professional societies recommend partial meniscectomy for patients with irreparable meniscus tears and mechanical knee symptoms that are refractory to at least 3 months of non-surgical care [5,19].…”
Section: Introductionmentioning
confidence: 99%
“…The number of meniscal allograft transplantations (MAT) has increased dramatically over the past 5 years. [1] MAT are indicated in patients who are functionally meniscus-deficient to improve outcome by decreasing contact pressures within the joint. [2][3][4] Those treated with MAT have shown improvement in symptoms and function in the mid and long-term.…”
Section: Introductionmentioning
confidence: 99%
“…Partial meniscectomy has been the gold standard for surgical treatment of meniscal tears for many years; it is safe with a low rate of complications and reoperation. 2 However, meniscectomy affects the knee biomechanics, 3 lowers the rate of return to play, 4 and with time could lead to osteoarthritis. 5 Although it was once believed that meniscal tears in the avascular zone, including parrot beak tears, did not possess the capacity to heal, repair of tears in the avascular zone could be clinically beneficial for young patients.…”
Section: Introductionmentioning
confidence: 99%